PUBLICATIONS OF DOCUMENTS IN UKRAINE IN THE SECOND HALF OF THE 20TH CENTURY: SOME ASPECTS OF THE PROBLEM - Dovzhuk, Igor (SWorld-Ger Conference proceedings, 2025)
The work examines the influence of documentary publications on the formation of the national information space, including in the modern conditions of mass dissemination of information and communication technologies, where unverified or false data are ofte